Modelling mode choice in passenger transport with integrated hierarchical information integration - Cornelia Richter; Stephan Keuchel (Journal of Choice Modelling, 2012)
The Integrated Hierarchical Information Integration (HII-I) approach allows to include a larger number of attributes in choice experiments by summarising similar attributes into constructs. In separate sub-experiments, one construct is described by its attributes while the other constructs are included by summarising construct values. This approach allows for testing of process equality in order to know if the different sub-experiments may be concatenated into an overall model. In this paper, the HII-I approach is applied to model the mode choice between a regional train, a (hypothetical) regional bus and a car (only available for car users). Test results show that process equality is given when analysing only the data of the bi-modal sub-experiments whereas the assumption of process equality is rejected for data of the tri-modal sub-experiments, where differences in error variances between the sub-experiments are found. This empirical finding suggests that it is possible to construct separate sub-experiments while arriving at a single concatenated model.
Keywords: 330; integrated choice experiments; hierarchical information integration; public transport; service quality; discrete choice experiments